Ensaios sobre migrações e impactos ambientais - Costa, Alessandra Leandro da (2019)
The process of transformation and degradation of the environment is a global issue under debate; the indiscriminate and predatory exploitation of the environmental stock increase natural costs daily. At the same time, the world registers the largest number of forcibly displaced persons. Global Trends (2017) recorded that in 2017 68.5 million people left their place of origin in search of refuge in other countries. Refugees aim to escape from persecution politics, violence, war and the violation of fundamental rights towards to prevent life in its fullness. The most of refugees--6.3 million--are from Syria, a country that has been in a civil war since the year 2011. Drawing this context, the themes of sustainable development and refuge are related to the question whether, in a country such as Germany, which aims to improve sustainable development indicators, population growth, in a short time, could influence this state determination. Drawing attention to people entering in the German territory as refugees are concerned about the environment and contribute to achieving environmental improvement goals. Qualitative research, with quantitative data collection and descriptive perspective, is carried out to analyze the environmental impacts caused by the mass migration of immigrants from Syria to Germany, in a short time. To reach the research goal, a historical context was established as the basis for the discussion about Germany and about migration as a way to open space to understand the elements that make up the sustainable development scenario, seeking to identify continuities and ruptures in the environment in question. Also, a literature and documentary review, as well as semistructured interviews were carried out with 15 Syrian refugees based in Germany from 09 to 30 October 2018. It was noticed that although the number of refugees demographically caused an impact; there were no significant transformations in the environment nor any other determinant influences in the Germanic goal of developing itself sustainably.